2022
DOI: 10.3390/foods11030252
|View full text |Cite
|
Sign up to set email alerts
|

Punicic Acid and Its Role in the Prevention of Neurological Disorders: A Review

Abstract: Millions of people worldwide are affected by neurodegenerative diseases (NDs). NDs are characterized by progressive damage and death of nerve cells accompanied by high levels of inflammatory biomarkers and oxidative stress conditions. Punicic acid, the main bioactive component of pomegranate (Punica granatum) seed oil, is an omega-5 isomer of conjugated α-linoleic acid that has shown strong anti-oxidative and anti-inflammatory effects that contributes towards its positive effect against a wide arrange of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Our previous study also revealed that the ratio of linoleic acid (LA) to oleic acid (OA) displayed a highly significant positive correlation with the inhibition rates in Job's tears (Coix lachryma-jobi L.) seed oil for human bladder carcinoma T24 cells [34]. TA is an omega-5 isomer of conjugated α-linolenic acid (CLnA) known for its broad biological effects, including anti-inflammatory, anti-diabetic, anti-obesity, antiproliferative, anti-carcinogenic, and antioxidant properties [35]. Seed oil exhibiting high antioxidant activity is characterized by a high content of total UFA content and a high ratio of TA/OA.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also revealed that the ratio of linoleic acid (LA) to oleic acid (OA) displayed a highly significant positive correlation with the inhibition rates in Job's tears (Coix lachryma-jobi L.) seed oil for human bladder carcinoma T24 cells [34]. TA is an omega-5 isomer of conjugated α-linolenic acid (CLnA) known for its broad biological effects, including anti-inflammatory, anti-diabetic, anti-obesity, antiproliferative, anti-carcinogenic, and antioxidant properties [35]. Seed oil exhibiting high antioxidant activity is characterized by a high content of total UFA content and a high ratio of TA/OA.…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive compounds of pomegranate peels are phenolic acids including gallic, caffeic, ferulic, cinnamic, ellagic acids apart from that, flavonoid compounds like catechin, epicatechin, anthocyanin, Proanthocyanidin, rutin, hesperidin etc. and also tannin like ellagitannins, Gallo tannins, corilagin, hexoside, Pedunculagin are present (Guerra-Vázquez et al, 2022). Pomegranate peels help in prevention of type II diabetes, oral cavities, Alzheimer disorder, cardiovascular manifestations, cancer and so on.…”
Section: Pomegranate Peelsmentioning
confidence: 99%
“…Punicic acid (PU) is a polyunsaturated omega-5 fatty acid, with a trans double bond conformation, at the eleventh carbon atom, and possesses high antioxidant and anti-MS activity, as it is shown by the beneficial effects of pomegranate seed oil (PSO), mainly comprising PU [ 98 , 99 ]. PSO, especially in nanodroplet formulation (Nano-PSO), showed significant beneficial effects, in EAE induced C57Bl naïve female mice, in much lower concentration (10% dose of the lowest active concentration of PSO) of the oil, reducing disease burden and preventing the disease onset, administered from the first day of EAE induction [ 98 ].…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%